2021
DOI: 10.1002/smi.3041
|View full text |Cite
|
Sign up to set email alerts
|

Drammatic breaks: Break recovery experiences as mediators between job demands and affect in the afternoon and evening

Abstract: The present study focused on within-workday recovery, which has received less scholarly attention than has recovery outside work. We examined six break recovery experiences (detachment, relaxation, autonomy, mastery, meaning and affiliation) as possible mediators between daily emotional job demands, positive and negative affect both in the afternoon and in the evening. We conducted a one-work week diary study (N = 107) among Finnish schoolteachers with three daily measurements per workday.Most participants (88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 105 publications
(235 reference statements)
3
33
0
Order By: Relevance
“…Although time for long lunch breaks might be limited for teachers at school, school principals might encourage their teachers scheduling short rest breaks, which have been shown to reduce feelings of stress and fatigue and to strengthen social support and task performance [ 54 , 55 ]. Detachment during rest breaks might also lead to lower negative affect and higher positive affect in the afternoon [ 56 ]. However, not only individual level interventions might be crucial for teachers’ psychological detachment: Work conditions within the educational system should promote recovery and detaching from work.…”
Section: Discussionmentioning
confidence: 99%
“…Although time for long lunch breaks might be limited for teachers at school, school principals might encourage their teachers scheduling short rest breaks, which have been shown to reduce feelings of stress and fatigue and to strengthen social support and task performance [ 54 , 55 ]. Detachment during rest breaks might also lead to lower negative affect and higher positive affect in the afternoon [ 56 ]. However, not only individual level interventions might be crucial for teachers’ psychological detachment: Work conditions within the educational system should promote recovery and detaching from work.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of psychological detachment is harmful concerning teachers' job stress (Gluschkoff et al, 2016) but there remains a lack of research concerning the mediating role of psychological detachment among teachers (see Türktorun et al, 2020). Hence, the current study tested the mediational model in which teachers' higher job stress would hinder their psychological detachment from work (see Sonnentag and Kruel, 2006;Sonnentag and Fritz, 2015) and hindered psychological detachment would result in more negative affect (see Virtanen et al, 2021) and job stress (see Gluschkoff et al, 2016) on the subsequent day. Thus, we were interested in whether psychological detachment would mediate the effect of previous days' job stress on subsequent day's negative affect and job stress.…”
Section: Introductionmentioning
confidence: 92%
“…Looking at the effect of teachers' psychological detachment, Virtanen et al (2021) found that teachers' higher daily detachment predicts their lower afternoon negative affect. A study by Fritz et al (2010) further showed that teachers' psychological detachment during the weekend is linked to higher levels of certain positive emotions measured both directly after the weekend and later at the end of the following week at work.…”
Section: Teachers' Psychological Detachment From Work As a Mediatormentioning
confidence: 99%
See 2 more Smart Citations